Literature Study: Dynamics of Young Generation Political Ethics in the Digital Era - Supriyantomo, Nur Adi; Tatimmussa'adah, Raden; Aulia, Putri Varizza; Sukmana, Nana; Sihombing, Andreas Parlin Roberto; Danova, Mohammad Gavin; Furnamasari, Yayang Furi (Master Program of Sociology, Universitas Malikussaleh, 2024)
The significance of ethics in young people's use of social media for political involvement is profound. During general elections, divergent viewpoints are normal, but mutual respect is crucial. Engaging in political life requires maturity and integrity, reflecting political ethics as a personal obligation. Social media enables young people to interact, express thoughts, and exchange information, but it also exposes them to unethical activities such as cyberbullying, peer pressure, and spreading misleading information. Therefore, young people must be aware of the moral ramifications of their social media usage and engage in politics in a morally sound and responsible manner. Understanding the impact of their online actions and maintaining ethical standards are essential. This ensures that their political engagement contributes positively to the democratic process and fosters a respectful and informed political discourse. Ethical participation in politics is crucial for maintaining a healthy and functioning democracy, promoting fairness, and upholding the integrity of the electoral process.